Padrões e processos de diferenciação taxonômica da fauna de peixes de uma ecoregião da América do Sul - Fernandes, Rogerio Taygra Vasconcelos (Universidade Federal Rural do Semi-Árido, 2013)
Here, we quantified the patterns of change in the similarity of the fish fauna of the Upper Paraná ecoregion, caused by the introduction of non-native species and anthropogenic factors, such as the construction of dams and the elimination of a biogeographic barrier. Additionally, we evaluated the importance of changes in rates of turnover and richness species in homogenization/differentiation dynamics. For the study, we mapped the spatial distribution of fish species through occurrence data georeferenced of Brazilian zoological museums. To evaluate temporal changes in the composition of the fish fauna, the data with the distribution of the species were divided into two periods: historical period composed entirely of native species, and the contemporary period, consisting of historical fauna plus non-native species. Changes in similarity patterns between fish assemblages were quantified using the Jaccard dissimilarity index to the historical and contemporary periods. To evaluate the influence of the non-native richness species, number of dam and distance to the Itaipu Dam on changes of similarity, we performed simple and partial Mantel tests. The results showed that the fish fauna has become more dissimilar over time, due to increases in turnover rates and addition of species. Furthermore, factors related to the heterogeneity of the basins and propagules pressure after removal of a biogeographical barrier has determined the patterns of changes in the similarity of the fish fauna
Patterns and process of taxonomic differentiation of fish fauna of South America ecoregion
Keywords: Diversidade-β; Turnover; Pressão de propágulos; Alto Paraná; Invasão biológica; β-diversity; Turnover; Propagule pressure; High Paraná; Biological invasion; CIENCIAS AGRARIAS::MEDICINA VETERINARIA